OUTPUT MEASUREMENT FOR THE BANKS: A REVIEW AND ILLUSTRATION OF THE VARIOUS APPROACHES - Harchaoui, Tarek M. (Assurances, 1998)
As financial intermediaries and the hub of the payment system, banks perform a vital role in the economy. In Canada, like in many other countries, banks are a major provider of financial services and the movement to deregulate banks portends an even greater role for them in the provision of financial services. In addition, the externalities that banking generates through its role as the nation's primary financial intermediary and conduit for monetary policy are considered to be enough to require substantial government protection and supervision. One of the most problematic areas facing national income accounts is in measuring the output accruing to the banking sector. This has always been an especially difficult undertaking since there exists no firm consensus as to what constitutes financial output. It is the purpose of this paper to review and to illustrate the various approaches currently existing with a special reference to the Canadian experience.